(untitled) (Economic Journal of Nepal, 2022)
The trade-off between inequality and growth and what should be done about it are some of the most debated issues in economics. The study aims to assess the relationship between income inequality and economic growth in South Asia. With different kinds of literature assessing different relationships between these two variables, the effects of inequality on growth are still very ambiguous for researchers. The paucity of time series data on the ‘Gini Ratio’ for South Asia has been one of the primary reasons for a small or no contribution to the effects of inequality in growth in the region. Here, the study used the data on the income share ratio of the top 10 percentile and bottom 50 percentile from 1980 to 2015 as a proxy for inequality and see its relationship with growth using the ‘Generalized Method of Moments’ estimation technique. The study found that inequality has a significant positive relationship with growth, which provides the basis for a trade-off between equity and efficiency. This gives rise to important policy implications for policymakers dealing with inequality.